Veterinary herbal medicines in India - Rastogi, Shruti; Pandey, Manoj Kumar; Prakash, Jai; Sharma, Alok; Singh, Gyanendra Nath (Pharmacognosy Reviews)
India has a rich and diversified flora. It is seen that synthetic drugs could pose serious problems, are toxic and costly. In contrast to this, herbal medicines are relatively nontoxic, cheaper and are eco-friendly. Moreover, the people have used them for generations. They have also been used in day-to-day problems of healthcare in animals. 25% of the drugs prescribed worldwide come from plants. Almost 75% of the medicinal plants grow naturally in different states of India. These plants are known to cure many ailments in animals like poisoning, cough, constipation, foot and mouth disease, dermatitis, cataract, burning, pneumonia, bone fractures, snake bites, abdominal pains, skin diseases etc. There is scarce review of such information (veterinary herbals) in the literature. The electronic and manual search was made using various key words such as veterinary herbal, ethno-veterinary medicines etc. and the content systematically arranged. This article deals with the comprehensive review of 45 medicinal plant species that are official in Indian Pharmacopoeia (IP) 2014. The botanical names, family, habitat, plant part used and pharmacological actions, status in British Pharmacopoeia 2014, USP 36 are mentioned. Also, a relationship between animal and human dose, standardization and regulatory aspects of these selected veterinary herbals are provided.
Keywords: Indian Pharmacopoeia 2014; standardization; veterinary herbals